Functional outcomes in proximal humerus fractures: a prospective registry-based analysis - Tashfeen Ahmad; Zehra Abdul Muhammad; Amna Haroon (Journal of the Pakistan Medical Association, 2021)
Objective: To evaluate clinical and functional outcomes of proximal humerus fractures managed with different procedures and determining factors influencing outcomes. Methods: Data of this prospective cohort was obtained from the orthopaedic trauma registry at a tertiary care Hospital from June 2015 to October 2019. Sixty-nine adult patients with proximal humerus fracture managed either surgically or non-operatively were identified. Functional and clinical outcomes had been assessed using Quick Disability of the Arm, Shoulder and Hand score. Outcomes were assessed up to 12 months follow-ups and were compared between different treatment groups and between isolated versus proximal humerus with additional upper limb fractures. Results: In the 69 patients, 31 (45%) belonged to >55 years age group. Fifty-eight (84%) patients were operated of which 43 (62%) underwent Proximal Humeral Internal Locking System procedure. There was non-significant difference in clinical and functional outcomes between isolated versus proximal humerus fractures associated with other upper limb fractures at follow-ups 6 weeks onwards. At 3 months follow-up, there was significantly better outcomes in all treatment groups compared to PHILOS with bone graft/BMP (p=0.004-0.035). Males had significantly better recovery at 3 months as compared to females (p=0.04). Continuous...